Cardinal directions and environmental concepts of landscape in Kwanyama (Owambo) - Otten, Dirk (AAeO - Afrikanistik-Aegyptologie-Online, 2005)
This contribution examines some conceptual domains of environment among the Kwanyama speakers of northern Namibia, focussing on the linguistic expression as well as on their semantic facets and richness. In many cases, it will become clear that the designation of landscape and its scenic characteristics of landscape does not necessarily require specific terms. Instead, it often makes use of phraseological and descriptive devices, which must be regarded as strongly context dependent. The major part of this paper deals with different types of landscape, their conceptualisation as well as their linguistic expression. This includes mainly the domains of forest, savannah, seasonal grassland and their salient features and elements. Finally, the findings will be contrasted with results from my survey on place names conducted in the Owambo region as part of a Sonderforschungsbereich (SFB) 389 (1.12.2005) project.